Analysis of Factors Affecting the Success of Handling Ovarian Hypofunction in Cattle in Langkat Regency - Sitompul, Yuniarti; Umar, Sayed; Sinulingga, Simon Elieser (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Handling reproductive disorders aims to increase the beef cattle population and lead to beef self-sufficiency. One of the disorders in reproduction in cows is a case of ovarian hypofunction. In general, this case occupies the highest position in Langkat Regency. This study aims to analyze the factors that influence the successful handling of cattle ovary hypofunction in Langkat Regency. The variables analyzed were body condition score, therapeutic treatment and the type of cow rearing. This research is a non-experimental study using logistic regression method. The data that used in this study were secondary data which was collected with a cross sectional approach. The data was obtained from the documentation of the Department of Agriculture and the Office of Food Security in Langkat Regency. The population was 658 cows that was diagnosed with ovarian hypofunction. The number of samples used in this study were 249 samples calculated by the slovin method. The sampling method was simple random sampling. The results of the analysis showed that the highest score of the body condition of the study sample was moderate. Most therapy in cattle with successful ovarian hypofunction is treatment one and two. The type of cow rearing that used with the highest number is the intensive one. Based on the results of the analysis, it was found that all the independent variables, namely body condition score, treatment / therapy, and type of cow rearing had a P value less than 0.05. So that the overall variables have a significant effect on the success of Ovarian Hypofunction in cattle in Langkat Regency. The variable that has the greatest influence on the success of ovarian hypofunction is the variable of treatment / therapy. Treatment or therapy in cattle is suggested to be a top priority which is always developed by related parties in order to increase production through successful treatment of ovarian hypofunction in cattle in Langkat Regency.